Assessment of Cellular and Organ Function and Dysfunction using Direct and Derived MRI Methodologies - Constantinides, Christakis (IntechOpen, 2016)
Despite the tremendous growth in the field of magnetic resonance imaging (MRI) evidenced in the initial phases of its development in the early twentieth century, scientific focus has shifted in recent years toward the study of physiology and pathophysiology that span the spatial scales of the molecule, cell, tissue, and organ. Intensified research activities over the past 15 years have justified efforts toward molecular and cellular imaging, dual-modality imaging systems, real-time acquisitions, dedicated image processing techniques and applications, and the critical evaluation of their potential translational value for use in the clinic. The integrative focus on molecular-cellular-tissue-organ function and dysfunction has taken a primary role in modern, personalized medicine, and it is envisaged to continue to do so, as accumulated knowledge from basic and clinical science work continues to elucidate molecular, cellular, and physiological/pathophysiological pathways and mechanisms. In this scientific effort, MRI continues to play a critical and synergistic role from the perspectives of basic science, diagnosis, and clinical interventional/therapeutic approaches. Within the realm of the current role of MRI in modern medicine, this book summarizes state-of-the-art direct and derived MRI methodologies and approaches as applied toward the assessment of cellular and organ function and dysfunction. The contributions in this effort are not excessive but few, comprehensive, and distinguished and of high quality. The topic areas can be generalized to find applications in other scientific areas and span both brain and cardiac applications, extending interest to wider audiences.